P572 Coexisting Inflammatory bowel disease and Ankylosing spondylitis: Management and clinical outcomes. (30th January 2023) - Savin, E; Levartovsky, A; Gendelman, O; Lidar, M; Ben-Horin, S; Kopylov, U
Abstract: Background: Ankylosing spondylitis (AS), which occurs in about 10% of inflammatory bowel disease (IBD) patients, is more common in Crohn's disease and does not correlate with bowel activity. The occurrence of IBD in patients with AS is 5-10%. We aimed to investigate the patterns of treatment modifications following newly diagnosed AS in patients with IBD or a new IBD diagnosis in patients with AS. Methods: This is a retrospective observational study that included patients with coexisting IBD and AS that were followed simultaneously by the gastroenterology and the rheumatology departments of the Sheba Medical Center. Patients with a follow-up duration of at least 3 months since the second diagnosis were included. Results: The cohort consisted of 68 patients, 41 with a first diagnosis of IBD (fIBD-group) and 27 with a first diagnosis of AS (fAS-group). Patients in the fAS-group were younger (median age of 36 years, inter quartile range (IQR) 25-48 vs. 43 years IQR 35-56, p=0.043), had more Crohn's disease (92.6% vs. 68.3%, p=0.016), had a shorter interval up to the second diagnosis (median of 3 years, IQR 1-6 vs. 6 years, IQR 2-11.5, p=0.03), and had an increased rate of past/current biologic treatment (81% vs. 51%, p=0.019) compared with the fIBD-group. Therapy modifications rates were 78% in the fIBD-group and 96% in the fAS-group as presented in Figure 1. The most common modification for the fIBD-group was initiation of biologic therapy in 18/32 patients (Adalimumab 44%, Infliximab 33%, Golimumab 5.75%, Etanercept 5.75%, Certolizumab pegol 5.75%, Ustekinumab 5.75%). In the fAS-group, switching biologic agent to Adalimumab or Infliximab (42%) and ceasing NSAIDs (27%) were the most common. At 1-year follow-up there were no significant differences in clinical outcomes (treatment failure, surgery/hospitalization, clinical remission) between fIBD and fAS groups. However, patients in both groups with treatment modifications, had a trend for higher rate of IBD clinical remission than patients without (72% vs. 40%, p=0.066). No difference was found in AS clinical outcome. Conclusion: Treatment modifications are common among newly coexisting IBD and AS patients, preferably biologic drug modifications. These modifications may contribute to IBD clinical remission.